The Role of E-Marketing in Innovating and Developing Banking Marketing Strategies: An Empirical Study on Bank Alinma – Saudi Arabia, with the Mediating Role of Customer Perceived Digital Value - aburub, Abdelmoti (Journal of Posthumanism, 2025)
This study assesses how digital marketing practices affect innovative banking marketing at Alinma Bank in Saudi Arabia, focusing on practices such as social media marketing agility, mobile marketing personalization, and interactive digital campaign engagement. The study also examines the mediating role of customer-perceived digital value in the relationship. Data were collected through 350 questionnaires across 20 branches around the country; out of these, 250 responses were analyzed. This study employed descriptive statistics, a reliability test, exploratory and confirmatory factor analyses (EFA and CFA), multiple regressions, and mediation analysis with 5,000 bootstrap samples and 95% confidence intervals by using SPSS and AMOS. Findings indicate that all three digital marketing variables had a significant positive influence on innovation in banking marketing, and CPDV acted as a partial mediator. The study adds to academic knowledge but provides practical contributions for banks to improve customer engagement and competitive advantage in digital marketing strategy development.